WADA and imperialism? A philosophical look into anti-doping and athletes as coloniser and colonised. Issue 3 (3rd July 2018) - Macedo, Emmanuel
ABSTRACT: Post-colonial philosophical scholarship in the late 20th century advanced notions of exploitation and domination of the periphery post imperialistic control. Works by authors Peter Ekeh and Edward Said describe the institutional behaviour and ideology of a modern imperialist system. Additionally, Michel Foucault's analysis of power helps explain how imperialist systems deploy what Foucault called juridical power for the domination of subjects. Drawing from these authors helps expose the practical and ethical complications of an imperialist model. This paper uses these insights to show that the World Anti-Doping Agency (WADA) provides an analogous case of an imperialist system and how the practical and ethical flaws of mirroring this system serve as an ineffective and unethical model for anti-doping. Among the many issues related to mirroring an imperialist system, the majority of problems stem from the divide that emerges between anti-doping enforcers and athletes. Ultimately the paper offers a potential solution to the problems, concluding with Maria Lugones' idea of playful world travelling as an imperative first step and shift in ideology towards restructuring the anti-doping movement. Lugones' idea of playful world travelling promotes the immersion of people. This immersion can close the divide between anti-doping enforcers and athletes.